EHealth literacy and preferences for eHealth resources in parents of children with complex CHD. (19th September 2016) - Kasparian, Nadine A.; Lieu, Nathan; Winlaw, David S.; Cole, Andrew; Kirk, Edwin; Sholler, Gary F.
Abstract: Introduction: This study aimed to (a) examine eHealth literacy, beliefs, and behaviours in parents of children with complex CHD, and (b) identify parents' preferences for the content, format, features, and functions of eHealth resources for CHD. Materials and methods: Families (n=198) of children born between 2008 and 2011 and diagnosed with CHD requiring surgery were mailed a survey assessing a range of variables including eHealth literacy, beliefs, and behaviours as well as preferences for the format, functions, features, and content of eHealth resources for CHD. Results: A total of 132 parents (83 mothers, 49 fathers) completed the survey (response rate: 50%). Mothers (96%) were more likely to access eHealth resources than fathers (83%, χ 2 =6.74, p=0.009). Despite high eHealth resource use, eHealth literacy was relatively low, with results demonstrating considerable and widespread gaps in awareness of, access to, and communication about eHealth resources. Over 50% of parents reported that decisions regarding their child's healthcare were influenced, to some extent, by web-based resources. Barriers to doctor–patient communication about eHealth included limited consultation time and concern about doctors' disapproval. Participants demonstrated a strong desire for "eHealth prescriptions" from their child's healthcare team, and perceived a wide range of eHealth topics as highly important, including treatment-related complications as well as physical, cognitive, and emotional development in children with CHD. Discussion: Results suggest a need for stronger, more proactive partnerships between clinicians, researchers, educators, technologists, and patients and families to bring about meaningful innovations in the development and implementation of eHealth interventions in paediatric cardiology.